RX-320 Rocket Static Pressure Combustion Chamber Prediction and Validation by Using Invers Method - Sofyan Sofyan; Vicky Wuwung (Jurnal Teknologi Dirgantara, 2018)
The static pressure data of the combustion chamber which can generally be obtained by performing direct measurements when static test is performed on the rocket is an important parameter in predicting the thrust and design of the combustion chamber of the rocket. However, there is a model rocket for flight test that is used in static test. Thus, there is no mounting for static pressure sensors (for measurement) are made. To solve the problem, then the inverse method is used as an iterative solution for the basic equations of the rocket thrust force in the nozzle by guessing the value of the static pressure of the combustion chamber firstly and calculate the iteration by including the value of the rocket thrust from static test data and the efficiency variation of the nozzle. The results of this calculation are then validated by using a 3D-CFD numerical simulation to obtain a more detailed comparison on the nozzle. In this research RX 320 LAPAN rocket nozzle with focus on maximum static thrust data of static test results is used. The 3-D numerical simulation is performed using Numeca CFD software, with k-extended wall extended turbulent model, numerical multigrid level 3 scheme, center based, and convergence criteria of 10 e-05. The result of calculation by inverse method and its comparison with numerical simulation shows that the smallest difference of the combustion chamber static pressure between inverse method and numerical simulation is 0.017%, that is achieved at 92% nozzle efficiency. At this point, the static pressure of the combustion chamber is 57.94 bar. From this point of view, the results of this comparison indicate that the inverse method can be used accurately for static pressure of the combustion chamber prediction, if the nozzle efficiency is given correctly. Furthermore, with given static pressure of the combustion chamber correctly, it will be very helpful in the design of the more optimum combustion chamber.